(untitled) (Педагогіка вищої та середньої школи, 2022)
There is a dependence of the development of teacher’s Creative style from the present conditions of school work. The organization of creative climate during the method work as one of the conditions is a high possibility of teacher’s positive attitude to professionalfursonal work.